HUBUNGAN STRES DENGAN GASTRITIS DI LEMBAGA PEMASYARAKATAN (LAPAS) KELAS IIA KOTA TARAKAN KALIMANTAN UTARA - Revi Yulia; Fatimah Ura Pabane, Isnina Noor Sakinah, Aulia Ramadhina (CV. Adiba Aisha Amira, 2024)
Gastritis can affect all ages and genders. Some surveys show that gastritis most often attacks productive age, at a productive age vulnerable to gastritis symptoms due to the level of busyness so that irregular eating patterns and experiencing stress due to the influence of environmental factors. The purpose of this study was to analyze the relationship between stress and the incidence of gastritis. The research was conducted in April 2021. The research method used descriptive analysis with a cross sectional approach on 52 respondents with purposive sampling technique. Data collection used instruments in the form of a stress questionnaire from DASS 42 (Depression Anxiety Stress Scale 42) consisting of 14 statement items and a respondent characteristics questionnaire consisting of the respondent's name, gender, age, education and history of gastritis. Statistical test results with Kendal's tau-b test showed a value of p=0.009 (<0.05). The conclusion of this study shows that there is a relationship between stress and gastritis in Tarakan City Correctional Institution (Lapas), North Kalimantan. In the future, it is hoped that the Tarakan City Class IIA Correctional Institution (Lapas) can pay attention to psychological problems in prisoners in prison so that prisoners do not experience stress that causes gastritis.